EFFECTS PARTICLES CONCENTRATION OF Al2O3 AND TiO2 TO CONVECTION COEFFICIENT ON DOUBLE PIPE HEAT EXCHANGER - Ario Geraldi; RR. Sri Poernomo Sari (Jurnal Ilmiah Teknik, 2022)
Heat exchanger is a device used to transfer heat energy from a fluid to in another fluid. Each fluid has different characteristics. Value of convection heat transfer is determined by the value of the convection heat transfer coefficient (h) which depends on the dimensions and flow conditions. The fluid with the additional of Al2O3 nanoparticles (aluminum oxide) and TiO2 (Titanium dioxide) has great potential for cooling applications. The purpose of this study was to analyze the effect of Al2O3 and TiO2 particle concentration on the value of the convection heat transfer coefficient in the double pipe heat exchanger with circular straight pipes. Cooling fluid used is pure water, the fluid with the addition of Al2O3 nanoparticles and fluid with the addition of TiO2 nanoparticles at concentrations of respectively 40 ppm and 60 ppm. Flow used in a heat exchanger is the flow of counterflow type. Changes in temperature controlled 95 ° C for hot fluid, 17ºC for cooling fluid. The results show the influence of Al2O3 and TiO2 nanoparticles in the fluid characteristics and an increase in the value of the convection heat transfer coefficient is influenced by the amount of concentration on mixing nanoparticles in the cooling fluid.